Pengaruh Kepemimpinan Transformasional dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening (Studi pada Petugas Pelayanan Gangguan di PT PLN (Persero) ULP Kudus Kota) - Budi Hartono; Nunik Kusnilawati; Djoko Santoso; Christantius Dwiatmadja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of transformational leadership and work environment on employee performance, as well as to examine the role of work motivation as an intervening variable in these relationships among disturbance service personnel at PT PLN (Persero) ULP Kudus Kota. This research employs a quantitative approach by collecting data through questionnaires and analyzing it using the Partial Least Square (PLS) method with SmartPLS software. The population consists of 75 disturbance service personnel, and the sampling technique uses total sampling. After data screening to avoid bias, 74 respondents were included in the analysis. Data analysis includes outer model and inner model testing to examine the relationships among variables. The results show that transformational leadership does not have a direct effect on employee performance, while the work environment has a positive and significant effect on performance. Transformational leadership and work environment both have a positive effect on work motivation, and work motivation positively affects employee performance. Furthermore, work motivation is proven to mediate the relationship between transformational leadership and work environment on employee performance. The study concludes that improving employee performance is more effectively achieved through creating a conducive work environment and enhancing work motivation, while transformational leadership plays an indirect role through increasing work motivation. Keywords: Transformational Leadership, Work Environment, Work Motivation